On farm intervention studies on reduction of boar taint prevalence: Feeding strategies, presence of gilts and time in lairage. (June 2018) - Heyrman, E.; Millet, S.; Tuyttens, F.A.M.; Ampe, B.; Janssens, S.; Buys, N.; Wauters, J.; Vanhaecke, L.; Aluwé, M.
Abstract: One of the challenges in the production of entire male pigs is the occurrence of boar taint. We separately tested the effect of 3 management strategies to reduce boar taint on respectively 2, 3, and 6 Flemish pig farms: 1) adapted feeding strategies, 2) presence of gilts in the compartment, and 3) varying lairage duration at the slaughterhouse. A commercialized feed concept resulted in a significant reduction of olfactory boar taint prevalence when fed for 2 weeks (T2W) compared to control (T-CON) ( P = 0.030 ). For T2W and when fed for 3 weeks (T3W), androstenone (AND) ( P = 0.002 for T2W, P = 0.029 for T3W) and skatole (SKA) ( P < 0.001 for T2W and T3W) were significantly reduced compared to T-CON. Olfactory boar taint prevalence was significantly reduced when feeding 5% dried chicory roots (FI5%) (P = 0.032), but not for 3% dried chicory roots (FI3%) (P = 0.958) . SKA concentration was significantly lower when feeding FI5% (P < 0.001) and when feeding FI3% (P = 0.034) . Rearing entire male pigs separately from gilts and increasing lairage duration from <1 h to >3 h did not significantly affect boar taint. Highlights: Feeding the TAINTSTOP feed concept for 2 or 3 weeks reduces boar taint. Feeding 5% and to a lesser extent 3% dried chicory roots reduces skatole. Boar taint prevalence and compounds were not different for entire male pigs reared with or without gilts present in the compartment. Boar taint prevalence and compounds were not different for entire male pigs spending long or short time spent in lairage.